Long-term monitoring of seed dispersal by Asian elephants in a Sundaland rainforest - Tan, Wei Harn (2020)
Elephants have profound effects on the functioning of the ecosystems they inhabit. Little is known, however, about the role of Asian elephants (Elephas maximus) as agents of seed dispersal in tropical rainforests of Southeast Asia, particularly in the Sundaland region. Sundaic forests are peculiar in their phenology, with supra-annual and highly irregular episodes of mast fruiting. Here I present a long-term (73-month) monitoring of the seeds dispersed by elephants in dipterocarp forests of northern Peninsular Malaysia. I conducted monthly dung surveys in two mineral licks (11.3 km apart) frequently visited by elephants. Additionally, I recorded haphazard observations of seeds and seedlings in elephant dung. I recorded a minimum of 45 morphospecies from at least 25 plant families dispersed by elephants. Elephant seed dispersal varies spatially, with only 39.4% of the morphospecies dispersed at both sites (Jaccard dissimilarity index = 0.45). Temporally, elephants dispersed seeds in sporadic pulses in terms of abundance and diversity, without any apparent seasonality (seeds appeared in 19.1 % of 1,284 dung piles and 49.3 % of 73 months sampled). Around 14 morphospecies exhibited the two types of megafaunal syndrome traits defined by Guimaraes et al. (2008). However, another 11 morphospecies were found to conform to a Type 3 trait; species with large fruits and moderately large (> 1.5 cm) seeds in moderately large numbers (> 15). This makes the total of 24 morphospecies exhibiting megafaunal syndrome traits. However, the current definition is over simplified, and a new definition is needed that expands beyond physical fruit traits. Over half (53%) of the plants dispersed by elephants exhibit the megafaunal dispersal syndrome, suggesting a higher level of specialized elephant-plant seed dispersal interactions than previously assumed in Asia. Sundaland’s forests are undergoing a rapid loss of their rich megafaunal assemblages, with profound and long-term consequences for their function.